Toward electrochromic device using solid electrolyte with polar polymer host - Nguyen, Chien A. (2012)
Polymer electrolyte is an important component in many multilayer devices such as batteries, fuel cells, and electrochromic devices. The effects of polymer electrolyte solidification on the ionic movement and device performance are presented based on near-infrared (IR) (860−2500 nm) electrochromic (EC) devices using the conducting polymer polyaniline. EC devices using electrolyte with polar polymer host of P(VDF-TrFE) show stable and reversible light modulation up to 65% in gel state and 30% in solid state. This is significantly improved when compared to devices with solidified nonpolar polymer host which retains less than 10% light modulation. Electrochemical impedance combined with in situ light modulation measurement identifies various key characteristics exerted by the electrolyte states on device performance. Gel-state devices are affected by the amount of dissociated ions while ionic movement in the electrolyte bulk and through the electrolyte/EC material interface dictates the light modulation in semisolid devices. For solid-state devices, electronic leakage, ionic dissociation, and interaction with electrochrome molecules have been found to limit the operation.